2019
DOI: 10.1177/0825859719865545
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Poetry on Empathy and Professional Burnout of Health-Care Workers: A Systematic Review

Abstract: Background: Narrative medicine (NM) interventions have positively influenced empathy and burnout to varying degrees in health-care workers. We systematically reviewed the impact of poetry, a form of NM, on empathy and professional burnout. Methods: A comprehensive search of Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations, and Daily, Ovid EMBASE, Ovid PsycINFO, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews, and Scopus, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Whereas previous systematic reviews have concluded that NM education may be beneficial in contributing to compassionate care,24 enhanced empathy25 29 and effective teaching,28 our research builds on the current literature to reveal a broad range of NM benefits. Our findings demonstrate that NM has shown potential for enhancing communication and team-building skills, encouraging perspective-taking and reflection, promoting empathic behaviour, detecting/mitigating burnout, cultivating narrative competence, augmenting pedagogical and clinical skills, and fostering ethical inquiry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas previous systematic reviews have concluded that NM education may be beneficial in contributing to compassionate care,24 enhanced empathy25 29 and effective teaching,28 our research builds on the current literature to reveal a broad range of NM benefits. Our findings demonstrate that NM has shown potential for enhancing communication and team-building skills, encouraging perspective-taking and reflection, promoting empathic behaviour, detecting/mitigating burnout, cultivating narrative competence, augmenting pedagogical and clinical skills, and fostering ethical inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Milota et al investigated the use of NM as an educational tool for medical students and concluded that, while NM comprises an effective teaching strategy, more research is needed to determine its long-term impact 28. Finally, Schoonover et al found that poetry, a component of NM, may increase empathy and reduce burnout among healthcare professionals 29…”
Section: Introductionmentioning
confidence: 99%
“…poprzez humanizację studiów, jest priorytetowe dla pomyślnej ewolucji zawodu na rynku pracy. 22,45,51,53 Poezja lekiem na wypalenie zawodowe W dyskursie o wpływie poezji i współdzielenia się refleksją na jej temat wśród pracowników sektora ochrony zdrowia podkreśla się zapobieganie wypaleniu zawodowemu, 19,22 co potwierdziła ostatnio Schoonover et al 54 w krytycznym przeglądzie prac oryginalnych opublikowanych w języku angielskim. Zagadnienie wypalenia zawodowego i pogardy dla samego siebie za bycie bezinteresownym oraz poczucie depersonalizacji stanowi poważny problem, 55,56 szczególnie, że w Polsce coraz częściej ratownicy medyczni, pielęgniarki i lekarze zmagają się z nieuzasadnioną i mało efektywnie poskramianą agresją pacjentów.…”
Section: Szczególna Rola Poezji W Edukacji Medycznejunclassified
“…Rather, it can be seen as a call to action for oncologists to recognize the experience of trainees coping with death and a sense of powerlessness. Trainees benefit from structured opportunities to debrief and process their experiences (Gunasingam et Schoonover et al 2019) and medical humanities (Gowda et al 2018) may also have a positive impact. When appropriate, the oncologist might highlight the privilege of caring for patients and their families at the end of life.…”
Section: Recognize Empathic Distressmentioning
confidence: 99%